2019
DOI: 10.3390/foods8080290
|View full text |Cite
|
Sign up to set email alerts
|

Fermented Sea Tangle (Laminaria japonica Aresch) Suppresses RANKL-Induced Osteoclastogenesis by Scavenging ROS in RAW 264.7 Cells

Abstract: Sea tangle (Laminaria japonica Aresch), a brown alga, has been used for many years as a functional food ingredient in the Asia-Pacific region. In the present study, we investigated the effects of fermented sea tangle extract (FST) on receptor activator of nuclear factor-κB (NF-κB) ligand (RANKL)-stimulated osteoclast differentiation, using RAW 264.7 mouse macrophage cells. FST was found to inhibit the RANKL-stimulated activation of tartrate-resistance acid phosphatase (TRAP) and F-actin ring structure formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
(82 reference statements)
1
7
0
Order By: Relevance
“…Thus, the nuclear translocation after phosphorylation of Nrf2 implies that Nrf2 is activated for transcriptional activation of downstream enzymes, including HO-1, by binding to the AREs. Recently, we demonstrated that the activation of Nrf2 by FST contributed to the inhibition of osteoclastogenesis through blockade of oxidative stress [27]. Supporting this result, our data showed that FST could further activate Nrf2 in the presence of H 2 O 2 , as evidence for the predominant nuclear expression of p-Nrf2 in H 2 O 2 and FST-cotreated cells.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Thus, the nuclear translocation after phosphorylation of Nrf2 implies that Nrf2 is activated for transcriptional activation of downstream enzymes, including HO-1, by binding to the AREs. Recently, we demonstrated that the activation of Nrf2 by FST contributed to the inhibition of osteoclastogenesis through blockade of oxidative stress [27]. Supporting this result, our data showed that FST could further activate Nrf2 in the presence of H 2 O 2 , as evidence for the predominant nuclear expression of p-Nrf2 in H 2 O 2 and FST-cotreated cells.…”
Section: Discussionsupporting
confidence: 81%
“…In addition, the application of FST is attracting attention as a potential tool to improve physiological functions such as memory improvement, anti-inflammatory, obesity reduction, and stress management [21,22,[24][25][26]. Recently, we reported that FST inhibited osteoclastogenesis, which was due to the blockade of oxidative stress involved in the activation of the nuclear factor erythroid 2-related factor 2 (Nrf2) pathway [27]. However, the effects and mechanisms of FST in oxidative stress-induced osteoblast dysfunction remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…FST extract was provided by Professor Young Hyun Choi of Dongeui University (Busan, Republic of Korea) 19 . Sea tangle was added to water at a ratio of 1:15 (w/v), and yeast extract and glucose were added according to the amount of sea tangle added.…”
Section: Methodsmentioning
confidence: 99%
“…The excessive activation of osteoclasts is the main pathological response of periodontitis. Different scholars have found that the intracellular ROS level can be reduced and Nrf2/NF-κB/NFATc1 signaling pathway can be regulated to inhibit osteoclast formation and alveolar bone resorption by inducing the transcription of antioxidant genes mediated by Nrf2 [15,16]. Nrf2 is known to regulate osteoclast differentiation and function by decreasing ROS via induction of anti-oxidant enzymes, such as sulfiredoxin (Srx) and peroxiredoxin (Prx).…”
Section: Effect Of Nrf2/are Signal Pathway In Periodontitismentioning
confidence: 99%